EVALUATION OF MANAGEMENT NETWORK SECURITY USING SEKCHECK NETWORK EVALUATOR - Rizal Syahri; Cholil W; Widiyati Q (Jurnal Informatika, 2014)
The Utilization of Information Technology in business has become a significant part in supporting the business process. The implementation of IT has been implemented as a value chain system which support the business transaction from first level process till documentation, its result a report which could mark the decision making process in manager level. Indeed the information which is the output of the system has a very important role in the process business; therefore the procedure and mechanism how to protect that information also need a special courtesy. There are several tools which has been use as security evaluator both inn system and network. This paper has concern about one of those tools, the tools called Sekcheck Network Evaluator Security Evaluator. This tools has function to analyze the current system in awareness of user in information security substances especially assessment of user role and activities in a network. The papers will analyze the assessments process by Sekcheck Network Evaluator and how the result is and how to accomplish it with Information Technology Audit process that will influence to the factors of awareness and risk level of information security from user perspective. At the end this could use as consideration input for managers to optimize user awareness about security of information in business.Keywords: Business transaction system, Information Security, Awareness, Assessment, Network, application Sekcheck Network Evaluator security evaluator